THE EFFICIENCY OF APPLYING INTERACTIVE LEARNING METHODS IN MEDICAL UNIVERSITIES - Kasymova Shaxlo Shavkatovna; Mukhitdinova Mavdjuda Imadovna; Khakberdieva Guljaxon Erkinovna (Galaxy International Interdisciplinary Research Journal, 2022)
During the years of independence in the Republic of Uzbekistan in accordance with the Law "On Education" and the National Program for Training.In order to radically improve the quality of training of the level and qualifications of the teaching staff of universities, the introduction of an improved system of their regular retraining in accordance with modern requirements: - teaching staff of universities, their in-depth study of the norms of legislation, the latest achievements in the field of theory, scientific and applied research, technological progress and innovation in the discipline taught, as well as modern methods of organizing the educational process; fundamental updating of qualification requirements, curricula